Enhancement of Acetone Gas-Sensing Responses of Tapered WO3 Nanorods through Sputtering Coating with a Thin SnO2 Coverage Layer - Yuan-Chang Liang; Yu Chao (Nanomaterials, 2019)
WO3−SnO2 composite nanorods were synthesized by combining hydrothermal growth of tapered tungsten trioxide (WO3) nanorods and sputter deposition of thin SnO2 layers. Crystalline SnO2 coverage layers with thicknesses in the range of 13−34 nm were sputter coated onto WO3 nanorods by controlling the sputtering duration of the SnO2. The X-ray diffraction (XRD) analysis results demonstrated that crystalline hexagonal WO3−tetragonal SnO2 composite nanorods were formed. The microstructural analysis revealed that the SnO2 coverage layers were in a polycrystalline feature. The elemental distribution analysis revealed that the SnO2 thin layers homogeneously covered the surfaces of the hexagonally structured WO3 nanorods. The WO3−SnO2 composite nanorods with the thinnest SnO2 coverage layer showed superior gas-sensing response to 100−1000 ppm acetone vapor compared to other composite nanorods investigated in this study. The substantially improved gas-sensing responses to acetone vapor of the hexagonally structured WO3 nanorods coated with the SnO2 coverage layers are discussed in relation to the thickness of SnO2 coverage layers and the core−shell configuration of the WO3−SnO2 composite nanorods.